EVALUASI GERAK JATUH DAN JONGKOK DENGAN MENGGUNAKAN SISTEM PENDETEKSI JATUH BERBASIS SENSOR ACCELEROMETER - Gigih Gumilar; Hendi Handian Rachmat (Jurnal Elektro dan Telekomunikasi Terapan (e-Journal), 2020)
In this study, accelerometer sensor used as fall detection system in, Wearable, and Ambulatory in order to evaluate falling and squat movement. This system consists of two parts, the transmitter and the receiver. Both parts were equipped with a 2,4Ghz radio frequency wireless communication system to transmit data from accelerometer between the two parts. The accelerometer Sensor is placed on the transmitter to detect the three axes of gravity acceleration and the magnitude values in the event of fall and squat using the ATMEGA328 control unit. The transmitter parts is placed on the waist for the test to detect 2 types of fall positions i.e foward and backward and squat. From the test result of this study, the average value of three axis from the steady state condition of falling foward is 0,123g, -0,473g, -0,888g, backward is -0,084g, 0,495g, 0,628g, and squat is 0,739g, -0,262g, -0,493g. As for the magnitude of falling forward is 2,916g, backward is 2,580g, and squat is 0,344g.